2014
DOI: 10.1016/j.bmc.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits Plasmodium falciparum enoyl-acyl carrier protein reductase

Abstract: Enoyl-acyl carrier protein reductase (ENR), a critical enzyme in type II fatty acid biosynthesis, is a promising target for drug discovery against hepatocyte-stage Plasmodium falciparum. In order to identify PfENR-specific inhibitors, we docked 70 FDA-approved, bioactive, and/or natural product small molecules known to inhibit the growth of whole-cell blood-stage P. falciparum into several PfENR crystallographic structures. Subsequent in vitro activity assays identified a noncompetitive low-micromolar PfENR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…CE and CE -related compounds are generally described in the literature as promising candidates for the development of novel drugs targeting different human pathologies in virtue of the different biological activities that have been correlated to the administration of CE itself or CE -enriched plant extracts [ 2 , 5 , 6 , 7 , 8 , 11 , 12 , 29 ]. From a mechanistic point of view, these bioactivities can be ascribed to an aspecific cytotoxicity deriving from a complex of possible and simultaneously operating mechanisms of action potentially involving different protein targets via reversible or covalent binding [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CE and CE -related compounds are generally described in the literature as promising candidates for the development of novel drugs targeting different human pathologies in virtue of the different biological activities that have been correlated to the administration of CE itself or CE -enriched plant extracts [ 2 , 5 , 6 , 7 , 8 , 11 , 12 , 29 ]. From a mechanistic point of view, these bioactivities can be ascribed to an aspecific cytotoxicity deriving from a complex of possible and simultaneously operating mechanisms of action potentially involving different protein targets via reversible or covalent binding [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the others, CE can interact with the human variant of the 90kDa Heat Shock Protein ( h Hsp90), a ubiquitous protein chaperone in Eukarya known to participate in crucial signaling pathways connected with cell growth and survival in stress-inducing conditions [ 9 , 10 ]. More recently, the growth inhibitory activity of CE -containing plant extracts or of the isolated natural compound against both Plasmodium and Leishmania parasites was reported [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tallorin and co-workers, based on molecular docking and subsequent in vitro screening, have identified celestrol as a potent PfENR inhibitor [416]. Using molecular docking (AutoDock) coupled with three-dimensional quantitative structure activity relationships (3D-QSAR), Wadhwa and co-workers identified five phytochemicals (3α,20-lupanediol, ergosterol peroxide, 24-methylenecycloartan-3-ol, 2 -epicycloisobrachycoumarinone epoxide, and atalaphyllidine, Figure 16) as potential PfENR inhibitors [417].…”
Section: Plasmodium Targetsmentioning
confidence: 99%
“…Previous studies have accounted this strong inhibition to the stable ternary complex formed when triclosan noncovalently interacts with both FabI and NAD + . 12,13 Additionally, it is suggested that AcpP interacts with basic residues adjacent to the FabI substrate binding loop. This loop is disordered in the FabI–cofactor binary complex and becomes ordered upon binding of NAD + and triclosan.…”
mentioning
confidence: 99%
“…We found that 1 had an IC 50 value of 49.3 ± 0.2 µM (Figure S3), which was 1000-fold greater (reduced affinity) than triclosan (IC 50 value of ~0.04 µM). 13 While this activity was less than desired, the slow off-rate associated with triclosan may still allow it to sufficiently trap ACP–ER complexes. Hence, we turned our attention to preparation of the corresponding crypto - 1 -AcpP.…”
mentioning
confidence: 99%